Near tip strain evolution under cyclic loading - J. Tong; Y.-W. Lu; B. Lin; Y. H. Tai; J.R. Yates (Fracture and Structural Integrity)
The concept of ratchetting strain as a crack driving force in controlling crack growth has previously been explored at Portsmouth using numerical approaches for nickel-based superalloys. In this paper, we report the first experimental observations of the near-tip strain evolution as captured by the Digital Image Correlation (DIC) technique on a compact tension specimen of stainless steel 316L. The evolution of the near-tip strains with loading cycles was studied whilst the crack tip was maintained stationary. The strains were monitored over the selected distances from the crack tip for a given number of cycles under an incremental loading regime. The results show that strain ratchetting does occur with load cycling, and is particularly evident close to the crack tip and under higher loads. A finite element model has been developed to simulate the experiments and the simulation results are compared with the DIC measurements.